The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1164/rccm.201601-0002oc
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced Deficiency of Mucosal-associated Invariant T Cells in the Chronic Obstructive Pulmonary Disease Lung. Implications for Nontypeable Haemophilus influenzae Infection

Abstract: Rationale: Mucosal-associated invariant T (MAIT) cells are a recently described abundant, proinflammatory T-cell subset with unknown roles in pulmonary immunity. Nontypeable Haemophilus influenzae (NTHi) is the leading bacterial pathogen during chronic obstructive pulmonary disease (COPD) exacerbations and is a plausible target for MAIT cells.Objectives: To investigate whether MAIT cells respond to NTHi and the effects of inhaled corticosteroids (ICS) on their frequency and function in COPD.Methods: Eleven sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 63 publications
5
99
0
Order By: Relevance
“…MAIT are a group of innate-like T lymphocytes that which are highly abundant in human blood (~1–10% [100]) and in mucosal tissues such as the intestine and lungs [101104]. These cells are characterized by their expression of the invariant T-cell receptor (TCR) α chain, TRAV1–2 joined with TRAJ33 and a limited range of TCRβ chains, and abundant expression of CD161 and CD218 (IL18Rα) [102, 105, 106].…”
Section: Mucosal-associated Invariant T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAIT are a group of innate-like T lymphocytes that which are highly abundant in human blood (~1–10% [100]) and in mucosal tissues such as the intestine and lungs [101104]. These cells are characterized by their expression of the invariant T-cell receptor (TCR) α chain, TRAV1–2 joined with TRAJ33 and a limited range of TCRβ chains, and abundant expression of CD161 and CD218 (IL18Rα) [102, 105, 106].…”
Section: Mucosal-associated Invariant T Cellsmentioning
confidence: 99%
“…The frequency of MAIT cells in normal human lungs ranges from 2 to 20% of all T cells [104, 117]. Given their abundance in blood, many studies have examined blood MAIT cells in various respiratory diseases.…”
Section: Mucosal-associated Invariant T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrahepatic MAIT cells have been shown to be highly activated and express CD69, HLA‐DR and CD38, and are positioned around bile ducts within hepatic portal tracts 111, 118. Furthermore, as their name suggests, they are abundant within the gut, particularly in the jejunum and colon10, 119 through their expression of gut‐homing markers α 4 β 7 and CCR9,11, 13, 118 as well as the lungs 120…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 99%
“…Although they are able to recognize a wide variety of bacteria microorganisms, bacteria that do not express riboflavin synthesis pathways do not stimulate MAIT cells(114). Hinks and colleagues demonstrated that in 11 patients who were exposed to inhaled corticosteroids, peripheral serum and bronchial biopsies contained less MAIT cells compared to healthy controls(115). In in vitro studies, non-typeable Haemophilus influenzae (NTHi) infection of macrophages obtained from healthy subjects were exposed to fluticasone or budesonide.…”
Section: Introductionmentioning
confidence: 99%